The Cultural Production of Social Movements - Carley, Robert F. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
The Cultural Production of Social Movements offers a theory of cultural practices, protest tactics, strategic planning and deliberation, and movement organizational structures: "ideological contention." It is a theory of ideology "from below." The Cultural Production of Social Movements shows how conflicts-both with external political forces and disagreements, dissensus, and the decision-making process internal to social movements-produce knowledge and meanings that, in turn, impact upon and change the practices that contribute to how social movements are structured and organized. The Cultural Production of Social Movements theorizes the relationship between consciously held superordinate ideas, the changing composition of progressive and oppositional social struggles, and the social worlds they hope to inhabit. Analyzing the Black Panther Party, specifically Kathleen Cleaver's break with the Student Non-violent Coordinating Committee and her contributions to the Party, Operaismo (or Workerism) in Italy and the relationship between shifting organizational strategies, inventive tactics, and novel and expansive ways to theorize class struggles, and the communal composition of "Worker-Recovered Enterprise Movements" in contemporary Argentina, this book shows how movement ideologies change and how meanings structure organizations, mobilizations, and futures. Robert F. Carley is Associate Professor of International Affairs in the Bush School of Government and Public Service at Texas A&M University. He is Vice President and President Elect of the Cultural Studies Association and is co-editor of Lateral: Journal of the Cultural Studies Association. He is the author and editor of eight books, most recently Cultural Studies in the Interregnum (Temple University Press, Forthcoming), Cultural Studies Methodology and Political Strategy (Palgrave Macmillan), and Culture and Tactics: Gramsci, Race, and the Politics of Practice (State University of New York Press).
Chapter 1: Introduction -- Chapter 2: Ideological Contention -- Chapter 3: Incipient Practice and Culture -- Chapter 4: Incipient Practice, Class, and Ideology -- Chapter 5: The Factory Without Bosses -- Chapter 6: Incipient Practice and Subaltern Groups -- Chapter 7:Conclusion.
Keywords: Social sciences -- Philosophy; Culture -- Study and teaching; Political science -- Philosophy; Social Philosophy; Social Theory; Cultural Studies; Political Philosophy